2020
DOI: 10.1016/j.mran.2020.100137
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Coronavirus environmental monitoring can contribute to detecting asymptomatic SARS-CoV-2 virus spreaders and can verify effectiveness of workplace COVID-19 controls

Abstract: Highlights Coronavirus on workplace environmental surfaces is associated with presence of asymptomatic spreaders and can be used to verify effectiveness of COVID-19 control practices. Workplace locations with several positive Coronavirus contaminated surfaces were 10 times more likely to have SARS-CoV-2 employees than locations with few or no contaminated surfaces. Environmental surface testing results can be used to inform the need for employee testing.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 18 publications
4
33
0
Order By: Relevance
“…This study showed that there are associations between positive SARS-CoV-2 antibody results and high-risk behavior such as traveling, use of public transportation, contact with symptomatic patients, and working at high-risk places (like hospital staff, taxi drivers, and working in crowded places like peddlers). This finding is consistent with the study that showed there is a relation between the diagnosis of asymptomatic COVID-19 infected people and viruscontaminated environments (21). So continuous monitoring, restriction of the passage of people in crowded areas, and disinfecting environments with risk of contamination along with mass vaccination in a short period of time can be useful in decreasing patients and prevention of disease spread.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that there are associations between positive SARS-CoV-2 antibody results and high-risk behavior such as traveling, use of public transportation, contact with symptomatic patients, and working at high-risk places (like hospital staff, taxi drivers, and working in crowded places like peddlers). This finding is consistent with the study that showed there is a relation between the diagnosis of asymptomatic COVID-19 infected people and viruscontaminated environments (21). So continuous monitoring, restriction of the passage of people in crowded areas, and disinfecting environments with risk of contamination along with mass vaccination in a short period of time can be useful in decreasing patients and prevention of disease spread.…”
Section: Discussionsupporting
confidence: 91%
“…SARS-CoV-2 RNA can be detected from many different kinds of surfaces, places, and devices, including phones ( Marshall et al, 2020 ; Santarpia et al, 2020 ; Ye et al, 2020 ; Zhou et al, 2020 ). Furthermore, active SARS-CoV-2 virus is more likely to be recovered from some surfaces when expelled from individuals with seemingly high viral load ( Bullard et al, 2020 ; Jefferson et al, 2020 ; Sonnleitner et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Behavior changes in the form of implementing health protocols as a general rule can prevent transmission if there is no medical intervention yet (West et al, 2020). In addition to adjusting the criteria for IHC, it is also necessary to carry out health protocols in the office (Marshall et al, 2020), as described as follows; basic hygiene routines, frequent disinfection, fitness screening, social distancing, workplace flexibility, and reducing face to face meetings. Several health protocols have been implemented to help reduce biological pollutants in IHC 5 criteria through the application of basic hygiene routines by creating a habit of washing hands, providing soap and running water at several spots in the workplace, particularly in the area before the entrance (Figure 6).…”
Section: Ihc 10mentioning
confidence: 99%